Topological Resilience of Shipping Alliances in Maritime Transportation Networks - Tiago Novaes Mathias; Yoshihisa Sugimura; Tomoya Kawasaki; Yasuhiro Akakura (Logistics, 2025)
Background: The resilience of shipping alliances within the global maritime container network (GMCN) has critical implications for global trade. This study examines the topological robustness of strategic alliances (SAs) in liner shipping, focusing on their structural properties and responses to disruptions. Methods: Using pre-2019 container vessel schedule data, we constructed a weighted node-edge network model of the GMCN. Centrality metrics were computed to identify critical nodes, and simulations were conducted to evaluate network robustness under random failures (RFs) and targeted attacks (TAs). Results: The results highlight the GMCN’s scale-free topology, which fosters resilience against RFs but exposes vulnerabilities to TAs on high-centrality nodes like Singapore and Shanghai. Among alliances, 2M and Ocean demonstrated superior resilience, attributed to strategic port selection and extensive coverage, yet their reliance on central hubs presents significant risks. Conclusions: This study underscores the importance of alliance-specific strategies, such as infrastructure investments and redundancy planning, to mitigate vulnerabilities. By bridging gaps in existing literature, the research provides insights for policymakers and industry stakeholders to enhance the robustness and adaptability of maritime logistics networks. These findings contribute to ensuring stable global supply chains within an evolving trade environment.